Teaching with Media Violence to Explore a Public Health Problem: A Qualitative Study - Karin Sprow; Ann L. Swartz (Adult Education Research Conference, 2008)
This action research study engaged students in a collaborative examination of the construction of knowledge about violence, by introducing critical media literacy through viewing and analysis of a violent film in the context of a class considering multiple aspects of violence as a public health problem.
Keywords: media violence; critical media literacy; nursing education